2013
DOI: 10.1136/bjophthalmol-2013-303282
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of postoperative endophthalmitis after cataract surgery in China: a multicenter investigation of 2006–2011

Abstract: The incidence of acute postoperative endophthalmitis after cataract surgery in tertiary care hospitals of China was 0.033%. Intraoperative communication with vitreous was a major risk factor for developing endophthalmitis. Prophylactic use of a high-concentration vancomycin and tobramycin may play a positive role in the prevention of postoperative endophthalmitis after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
3
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
5
44
3
2
Order By: Relevance
“…Confusingly, recent studies have proposed that the incidence of postoperative endophthalmitis was not related to the incision location723. Here, in our study, we observed no relationship between the type of incision and the development of endophthalmitis (p = 0.718).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Confusingly, recent studies have proposed that the incidence of postoperative endophthalmitis was not related to the incision location723. Here, in our study, we observed no relationship between the type of incision and the development of endophthalmitis (p = 0.718).…”
Section: Discussioncontrasting
confidence: 61%
“…We found that the ECCE surgery rate was much higher in the small and medium-scale departments when compared with the top eye centers in China (10.3% vs 2.2%)2. The low coverage of phacoemulsification suggests an imbalance of medical resources in China, including the lesser skills of the surgeons and the lack of proper equipment in most Chinese hospitals.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A multicenter study reported that the incidence of postoperative endophthalmitis was significantly lower in cataract centers that used tobramycin as a prophylaxis against infection. 22 None of the previous studies on the incidence of endophthalmitis specifically analyzed the impact of using disposable adhesive drapes during ophthalmic operations. A systematic review 23 concluded that there was no evidence that disposable adhesive drapes could reduce surgical site infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Olgularımızda endoftalminin %0.046 gibi düşük oranda görülmesinde bu uygulamanın önemli bir rolü olduğu düşüncesindeyiz. Katarakt ameliyatların-dan sonra endoftalmi sıklığı %0.033-0.043 olarak bildirilmiştir (23,24). Katarakt ameliyatları intravitreal enjeksiyonlara kıyasla göziçinde daha çok cerrahi manipulasyon yapılan uygulamalardır.…”
Section: Discussionunclassified